Least Squares Estimator for Vasicek Model Driven by Fractional Levy Processes - wang, qingbo; Yin, Xiuwei (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In this paper, we consider parameter estimation problem for Vasicek model driven by fractional lévy processes defined We construct least squares estimator for drift parameters based on time?continuous observations, the consistency and asymptotic distribution of these estimators are studied in the non?ergodic case. In contrast to the fractional Vasicek model, it can be regarded as a Lévy generalization of fractional Vasicek model.